Learning versus the Common Core - Tampio, Nicholas (Forerunners (Minneapolis, Minn.), 2019)
An open challenge to Common Core's drive for uniformity. Learning versus the Common Core explains how standards-based education reform is transforming nearly every aspect of public education. With a nod to the philosophy of John Dewey, Tampio concludes with a vision of what democratic education can look like today--and how people can form rhizomatic alliances across different political and ethical backgrounds to fight the Common Core.